Iron-based nano-clay material with ordered functional elements as well as preparation method and application of iron-based nano-clay material

By acidizing and pyrolysis of nanocils, iron-based nanocil materials with functional motif sequence were prepared, which solved the problems of small specific surface area of ​​existing catalysts and small number of active sites, and achieved the effect of efficient activation of persulfates and effective removal of emerging pollutants.

CN119565607AActive Publication Date: 2025-03-07HUNAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411478468.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-03-07
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The existing supported iron-based catalysts have small specific surface area, small number of active sites, poor catalytic performance and poor structural stability, making it difficult to efficiently activate persulfate, and there is a risk of secondary pollution.

Method used

By acidizing and pyrolyzing the nanocil, an iron-based nanocil material with functional motif sequence was prepared. Through the acidizing and pyrolyzing of the nanocil, the material widens the inner diameter of the nanocil, corrodes the aluminum site in the inner diameter of the tube, promotes the adsorption and doping of iron, and forms a uniformly dispersed and firm iron active site.

Benefits of technology

Iron-based nanoclay materials with large specific surface area, large number of active sites, excellent catalytic performance and good structural stability were obtained. They can efficiently activate persulfate, significantly improve the removal efficiency of emerging pollutants, and reduce the risk of secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565607A_ABST
    Figure CN119565607A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-based nano-clay material with a functional element sequence and a preparation method and application thereof. The preparation method comprises the following steps: acidizing nano-clay, mixing the acidized nano-clay with ferrocene and an organic solvent to prepare a precursor, and pyrolyzing the precursor to obtain the iron-based nano-clay material with the functional element sequence. According to the preparation method disclosed by the invention, the nano-clay is acidified, ferrocene is taken as a doped iron source, and the iron-based nano-clay material which is large in specific surface area, large in number of active sites, excellent in catalytic performance and good in structural stability and is constructed by functional elements can be prepared through pyrolysis; when the persulfate catalyst is used for treating emerging pollutant wastewater, emerging pollutants can be effectively degraded, pH interference is small, catalytic efficiency can be achieved under the very wide pH condition, and the persulfate catalyst has the advantages of being simple in process, convenient to operate, low in cost, high in treatment efficiency, good in degradation effect and the like, and has wide application prospects. The method has important significance for effectively removing emerging pollutants in the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new environmental materials, and relates to an iron-based nano-clay material with a functional element sequence structure, a preparation method and an application thereof. Background Art

[0002] With the continuous advancement of industrialization and urbanization, various emerging pollutants such as drug residues, microplastics, and endocrine disruptors pose a serious threat to ecosystems (such as wetland ecosystems). These pollutants are not only difficult to remove through natural degradation processes, but may also accumulate and amplify through the food chain, ultimately affecting human health. Therefore, effectively removing emerging pollutants in the environment is a technical problem that needs to be solved at this stage.

[0003] The advanced oxidation process based on activated persulfate is an efficient and environmentally friendly water treatment technology. This system mainly uses persulfate (such as sodium persulfate or potassium persulfate) as an oxidant, which is activated under specific conditions to produce highly active sulfate radicals (SO4 ·- ) and hydroxyl radicals (·OH). Since these free radicals have strong oxidizing ability, they can effectively decompose organic pollutants in water. However, persulfate is often difficult to exert its superior oxidizing performance without a catalyst. Therefore, it is urgent to obtain a catalyst that can efficiently activate persulfate.

[0004] Iron is a well-known catalyst that can efficiently activate the persulfate system to produce free radicals, but it is easy to aggregate in water and fall off from the carrier, causing secondary pollution. Fixing iron on a carrier is an improved strategy to effectively prevent agglomeration and falling off, but the existing supported iron-based catalysts mainly load iron and its oxides on the surface of the carrier or fill them inside the carrier, which has the following defects: (1) It is difficult to effectively prevent iron metal ions from entering the treatment system due to dissolution, and it is still very easy to cause secondary pollution. In particular, when iron and its oxides are loaded on the surface of the carrier, the possibility of iron active substances falling off the carrier is still very high; (2) It is difficult to effectively increase the specific surface area of ​​the catalyst, resulting in a small number of active sites, and it is difficult to quickly activate persulfate. In particular, when iron and its oxides are filled inside the carrier, the specific surface area of ​​the catalyst is smaller, the number of active sites is smaller, and the catalytic performance is poor. Therefore, obtaining a supported iron-based catalyst with a large specific surface area, a large number of active sites, excellent catalytic performance, and good structural stability is of great significance for efficiently activating persulfate and achieving rapid and thorough removal of emerging pollutants. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide an iron-based nanoclay material with a functional element sequence having a large specific surface area, a large number of active sites, excellent catalytic performance and good structural stability, as well as a preparation method and application thereof.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A method for preparing an iron-based nanoclay material with a functional element sequence structure comprises the following steps:

[0008] S1. Acidifying the nanoclay;

[0009] S2, mixing the acidified nanoclay, ferrocene and organic solvent in step S1, stirring and drying to obtain a precursor;

[0010] S3. Pyrolyzing the precursor obtained in step S2 to obtain an iron-based nanoclay material with a functional element sequence.

[0011] The above preparation method is further improved, in step S1, the nanoclay is acidified with an acidic solution; the acidic solution is at least one of acetic acid solution, sulfuric acid solution and nitric acid solution; the volume ratio of acid to water in the acidic solution is 1:2-5.

[0012] The above preparation method is further improved, in step S1, the nanoclay is at least one of halloysite, sepiolite and montmorillonite.

[0013] The above preparation method is further improved in that in step S1, the acidification time is 12h to 24h.

[0014] The above preparation method is further improved, in step S2, the mass ratio of the acidified nanoclay to the ferrocene is 1-5:1; the organic solvent is at least one of ethanol, methanol and acetone; and the stirring time is 4h-24h.

[0015] The above preparation method is further improved, in step S3, the pyrolysis is carried out in a protective atmosphere; the gas in the protective atmosphere is any one of nitrogen, helium, neon and argon; the heating rate during the pyrolysis process is 5°C / min to 15°C / min; the pyrolysis temperature is 400°C to 600°C; the pyrolysis time is 2h to 4h.

[0016] As a general technical concept, the present invention also provides an iron-based nano-clay material with a functional element sequence structure, which is prepared by the above-mentioned preparation method.

[0017] The above-mentioned iron-based nanoclay material with functional element sequence is further improved in that the iron-based nanoclay material with functional element sequence comprises a nanoclay material doped with iron atoms; the nanoclay material has a nanotube structure.

[0018] As a general technical concept, the present invention also provides an application of the above-mentioned iron-based nanoclay material with a functional element structure as a catalyst for persulfate in the degradation of emerging pollutants.

[0019] The above application is further improved, using the iron-based nanoclay material with a functional element structure as a catalyst for persulfate to degrade emerging pollutants in water, including the following steps: mixing the iron-based nanoclay material with a functional element structure, water containing emerging pollutants, and persulfate for a catalytic reaction to complete the degradation of emerging pollutants in the water.

[0020] The above application is further improved in that the amount of the iron-based nanoclay material with the functional element structure added is 0.01g to 0.2g per liter of the water body containing emerging pollutants; and the initial concentration of persulfate in the catalytic reaction system is controlled to be 2mM.

[0021] The above application is further improved, wherein the initial concentration of emerging pollutants in the water body containing emerging pollutants is ≤10 mg / L; the emerging pollutants in the water body containing emerging pollutants are at least one of perfluorinated compounds, antibiotics, microplastics, and endocrine disruptors; the antibiotic is norfloxacin; the persulfate is peroxymonosulfate and / or peroxydisulfate; and the time of the catalytic reaction is ≥2 min.

[0022] Compared with the prior art, the advantages of the present invention are:

[0023] (1) In view of the shortcomings of existing supported iron-based catalysts, such as small specific surface area, small number of active sites, poor catalytic performance, poor structural stability, and the resulting defects such as difficulty in efficiently activating persulfate and high risk of secondary pollution, the present invention creatively provides a method for preparing an iron-based nanoclay material with a functional element sequence. The nanoclay is first acidified and the surface of the nanoclay is corroded, which can not only widen the inner diameter of the nanoclay tube, but also corrode some aluminum sites in the inner diameter of the tube, thereby facilitating the subsequent adsorption and doping of iron. On this basis, the acidified nanoclay and ferrocene are mixed in an organic solvent, and the ferrocene is dissolved in the organic solvent so that the ferrocene and the nanoclay are fully mixed. It is beneficial to promote the adsorption and loading of ferrocene by nanoclay, and finally the nanoclay loaded with ferrocene is pyrolyzed, and under high temperature, ferrocene is used as an iron source to dope iron atoms into the nanoclay, especially, during the acidification and pyrolysis process, the basic structure of the nanoclay is not destroyed, and the nanoclay doped with iron elements still presents the same nanotubular structure as the original nanoclay, which can not only increase the specific surface area of ​​the material, but also form uniformly dispersed and firm iron active sites on the surface and inside of the nanoclay, and effectively reduce the dissolution of iron while increasing the iron active sites, thereby obtaining an iron-based nanoclay material with a functional element sequence structure having a large specific surface area, a large number of active sites, excellent catalytic performance, and good structural stability. At the same time, the preparation method of the present invention also has the advantages of simple process, convenient operation, low cost, etc., is suitable for large-scale preparation, and is convenient for industrial application.

[0024] (2) The nanoclay used in the preparation method of the present invention has the advantages of wide source, low price and low toxicity, which can effectively reduce the material preparation cost and achieve environmental protection.

[0025] (3) The present invention also provides an application of an iron-based nanoclay material with a functional element structure as a catalyst for persulfate in the degradation of emerging pollutants. For example, the iron-based nanoclay material with a functional element structure is used as a catalyst for persulfate to degrade emerging pollutants in water. Specifically, the iron-based nanoclay material with a functional element structure, water containing emerging pollutants, and persulfate are mixed for catalytic reaction to complete the degradation of emerging pollutants in the water. The method has the advantages of simple process, convenient operation, low cost, high treatment efficiency, good degradation effect, etc., and can achieve effective degradation of emerging pollutants. In particular, the iron-based nanoclay material with a functional element structure is less affected by pH, can exert catalytic efficiency under a very wide range of pH conditions, and can show very high treatment efficiency and very good removal effect, which is of great significance for effectively removing emerging pollutants in the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0027] Figure 1 This is a SEM image of the original halloysite material used in Example 1 of the present invention.

[0028] Figure 2 This is a SEM image of the iron-based halloysite material (Fr-HNT) with a functional element structure prepared in Example 1 of the present invention.

[0029] Figure 3 This is a TEM image of the iron-based halloysite material (Fr-HNT) with functional element structure prepared in Example 1 of the present invention.

[0030] Figure 4 This is the iron fitting diagram of the X-ray photoelectron spectrum of the halloysite material (HNT) after acidification in Example 1 of the present invention.

[0031] Figure 5 This is the iron fitting diagram of the SX-ray photoelectron spectrum of the iron-based halloysite material (Fr-HNT) with functional unit structure prepared in Example 1 of the present invention.

[0032] Figure 6 This is a comparison chart of the removal of norfloxacin by the iron-based halloysite material (Fr-HNT) with the functional unit structure in Example 4 of the present invention, the acidified halloysite material (HNT), and the supported iron-based catalyst (Fe2O3-HNT).

[0033] Figure 7 This is a diagram showing the removal effect of norfloxacin by the iron-based halloysite material (Fr-HNT) with a functional element structure in Example 5 of the present invention under different pH conditions.

[0034] Figure 8 This is a diagram showing the removal effect of the iron-based halloysite material (Fr-HNT) with a functional element structure in Example 6 of the present invention on norfloxacin of different concentrations. DETAILED DESCRIPTION

[0035] The present invention provides a method for preparing an iron-based nanoclay material with a functional element sequence, comprising the following steps:

[0036] S1. Acidifying the nanoclay.

[0037] S2, mixing the acidified nanoclay, ferrocene and organic solvent in step S1, stirring and drying to obtain a precursor.

[0038] S3. Pyrolyzing the precursor obtained in step S2 to obtain an iron-based nanoclay material with a functional element sequence.

[0039] In the present invention, the nanoclay is acidified with acetic acid solution, and the acidification time is 12h to 24h, preferably, the acidification time is 14h to 22h, and more preferably, the acidification time is 15h to 20h.

[0040] In the present invention, the acetic acid solution used is obtained by mixing acetic acid and water, wherein the volume ratio of acetic acid to water is 1:2-5, preferably, the volume ratio of acetic acid to water is 1:3-4, and more preferably, the volume ratio of acetic acid to water is 1:3.5.

[0041] In the present invention, the nanoclay used is at least one of halloysite, sepiolite and montmorillonite. Preferably, the nanoclay used is halloysite and montmorillonite. More preferably, the nanoclay used is halloysite.

[0042] In the present invention, the mass ratio of the acidified nanoclay to ferrocene is 1-5:1, preferably, the mass ratio of the acidified nanoclay to ferrocene is 1-4:1, and more preferably, the mass ratio of the acidified nanoclay to ferrocene is 1.5-4:1.

[0043] In the present invention, the organic solvent is at least one of ethanol, methanol and acetone. Preferably, the organic solvent is ethanol or methanol. More preferably, the organic solvent is ethanol.

[0044] In the present invention, the acidified nanoclay and ferrocene are stirred in the organic solvent for 4 to 24 hours, preferably for 8 to 20 hours, and more preferably for 12 to 16 hours.

[0045] In the present invention, the pyrolysis is carried out in a protective atmosphere, and the gas in the protective atmosphere is any one of nitrogen, helium, neon and argon, preferably argon or nitrogen, and more preferably nitrogen.

[0046] In the present invention, the heating rate during the pyrolysis process is 5°C / min to 15°C / min, preferably 8°C / min to 12°C / min, and more preferably 9°C / min to 10°C / min.

[0047] In the present invention, the pyrolysis temperature is 400°C to 600°C, preferably 450°C to 550°C, and more preferably 500°C to 550°C.

[0048] In the present invention, the pyrolysis time is 2 h to 4 h, preferably 2.2 h to 3.8 h, and more preferably 2.1 h to 2.6 h.

[0049] In the present invention, the prepared iron-based nanoclay material with functional element sequence structure includes nanoclay material, the nanoclay material is doped with iron atoms, and the nanoclay material is in a nanotube structure.

[0050] The present invention also provides an application of an iron-based nanoclay material with a functional element structure as a catalyst for persulfate in the degradation of emerging pollutants. For example, the use of the iron-based nanoclay material with a functional element structure as a catalyst for persulfate to degrade emerging pollutants in water bodies comprises the following steps: mixing the iron-based nanoclay material with a functional element structure, water containing emerging pollutants, and persulfate for a catalytic reaction to complete the degradation of emerging pollutants in the water body.

[0051] In the present invention, the added amount of the iron-based nanoclay material with a functional element structure is 0.1 g to 0.2 g per liter of the water body containing emerging pollutants.

[0052] In the present invention, the initial concentration of persulfate in the catalytic reaction system is controlled to be 2 mM.

[0053] In the present invention, the initial concentration of emerging pollutants in the water body containing emerging pollutants is ≤10 mg / L, and the emerging pollutants in the water body containing emerging pollutants are at least one of perfluorinated compounds, antibiotics, microplastics, and endocrine disruptors, wherein the antibiotic is norfloxacin.

[0054] In the present invention, the persulfate used is peroxymonosulfate and / or peroxydisulfate.

[0055] In the present invention, the catalytic reaction time is ≥ 2 min.

[0056] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby. In the following embodiments of the present invention, unless otherwise specified, the materials and instruments used are commercially available, the equipment used is conventional equipment, and the data obtained are the average values ​​of more than three repeated experiments.

[0057] Example 1

[0058] A method for preparing an iron-based nanoclay material with a functional element sequence structure, specifically preparing an iron-based halloysite material with a functional element sequence structure, comprising the following steps:

[0059] S1. Acidification of the nanoclay, specifically:

[0060] The halloysite was naturally air-dried, acidified in a mixed solution of acetic acid and water (the volume ratio of acetic acid to water in the mixed solution was 1:3), stirred for 12 hours under magnetic stirring, the liquid was separated using a centrifuge, and the acidified halloysite was dried.

[0061] S2. According to the mass ratio of the acidified nanoclay to ferrocene being 2:1, the halloysite (HNT) dried in step S1, ferrocene (commercially available) and ethanol are mixed, stirred under magnetic conditions for 12 hours, and dried to obtain a precursor.

[0062] S3. Pyrolyzing the precursor obtained in step S2, specifically: placing the precursor in a tubular furnace, heating it to 550° C. at a heating rate of 10° C. / min under a nitrogen atmosphere, keeping it warm for 2 hours, and naturally cooling it to room temperature to obtain an iron-based halloysite material with a functional unit structure, named Fr-HNT.

[0063] In this embodiment, the prepared iron-based halloysite material with functional element structure includes a nano-clay material, the nano-clay material is doped with iron element, the nano-clay material is in a nano-tube structure, and the nano-clay material is halloysite.

[0064] Figure 1 This is a SEM image of the original halloysite material used in Example 1 of the present invention.

[0065] Figure 2 This is a SEM image of the iron-based halloysite material (Fr-HNT) with a functional element structure prepared in Example 1 of the present invention.

[0066] Figure 3 This is a TEM image of the iron-based halloysite material (Fr-HNT) with functional element structure prepared in Example 1 of the present invention.

[0067] Depend on Figures 1 to 3 It can be seen that in the preparation method of the present invention, the basic structure of the iron-based halloysite material obtained by acidification and pyrolysis is not destroyed, and still presents the same nanotube structure as the original halloysite material.

[0068] Figure 4 This is the iron fitting diagram of the X-ray photoelectron spectrum of the halloysite material (HNT) after acidification in Example 1 of the present invention.

[0069] Figure 5 This is the iron fitting diagram of the SX-ray photoelectron spectrum of the iron-based halloysite material (Fr-HNT) with functional unit structure prepared in Example 1 of the present invention.

[0070] Depend on Figure 4 and Figure 5 It can be seen that in the present invention, after acidification, mixing with ferrocene and pyrolysis, iron atoms are successfully doped into halloysite, which is beneficial to increase the number of active sites and structural stability.

[0071] Example 2

[0072] A method for preparing an iron-based nanoclay material with a functional element sequence structure, specifically preparing an iron-based montmorillonite material with a functional element sequence structure, comprising the following steps:

[0073] S1. Acidification of the nanoclay, specifically:

[0074] The montmorillonite was naturally air-dried, acidified in a mixed solution of acetic acid and water (the volume ratio of acetic acid to water in the mixed solution was 1:5), stirred for 16 hours under magnetic stirring, the liquid was separated by a centrifuge, and the acidified montmorillonite was dried.

[0075] S2. According to the mass ratio of the acidified nanoclay to ferrocene being 2:1, the montmorillonite dried in step S1, ferrocene (commercially available) and ethanol are mixed, stirred under magnetic conditions for 16 hours, and dried to obtain a precursor.

[0076] S3. Pyrolyzing the precursor obtained in step S2, specifically: placing the precursor in a tubular furnace, heating it to 500° C. at a heating rate of 9° C. / min under a nitrogen atmosphere, keeping it warm for 2.5 hours, and naturally cooling it to room temperature to obtain an iron-based montmorillonite material with a functional unit structure.

[0077] Example 3

[0078] A method for preparing an iron-based nanoclay material with a functional element sequence structure, specifically preparing an iron-based sepiolite material with a functional element sequence structure, comprising the following steps:

[0079] S1. Acidification of the nanoclay, specifically:

[0080] The sepiolite was naturally air-dried, acidified in a mixed solution of acetic acid and water (the volume ratio of acetic acid to water in the mixed solution was 1:4), stirred for 15 hours under magnetic stirring, the liquid was separated using a centrifuge, and the acidified sepiolite was dried.

[0081] S2. According to the mass ratio of the acidified nanoclay to ferrocene being 2:1, the dried sepiolite in step S1, ferrocene (commercially available) and ethanol are mixed, stirred under magnetic conditions for 15 hours, and dried to obtain a precursor.

[0082] S3. Pyrolyzing the precursor obtained in step S2, specifically: placing the precursor in a tubular furnace, heating it to 600° C. at a heating rate of 10° C. / min under a nitrogen atmosphere, keeping it warm for 2 hours, and naturally cooling it to room temperature to obtain an iron-based sepiolite material with a functional unit structure.

[0083] Comparative Example 1

[0084] A method for preparing a supported iron-based catalyst comprises the following steps:

[0085] Halloysite was naturally air-dried, the mass ratio of Fe2O3 to HNT was 1:2, halloysite and ferric oxide (Fe2O3) were acidified in a mixed solution of acetic acid and water (the volume ratio of acetic acid to water in the mixed solution was 1:3), stirred for 12 hours under magnetic conditions, and dried. The material obtained after drying was placed in a tubular furnace and pyrolyzed under a nitrogen atmosphere. The heating rate during the pyrolysis process was 5°C / min, and the temperature was kept at 550°C for 2 hours, and then naturally cooled to room temperature to obtain a supported iron-based catalyst named Fe2O3-HNT.

[0086] Example 4

[0087] The invention discloses an application of an iron-based nanoclay material with a functional element sequence structure as a catalyst for persulfate in the degradation of emerging pollutants, specifically using the iron-based nanoclay material with a functional element sequence structure as a catalyst for persulfate to activate peroxydisulfate to degrade norfloxacin (NOR) in water, comprising the following steps:

[0088] Take 10 mg of the iron-based halloysite material (Fr-HNT) with a functional element structure prepared in Example 1, add it to 100 mL of a 5 mg / L norfloxacin (NOR) solution (the pH value of the solution is 6.5), and add 1 mL of a 0.2 mol / L peroxydisulfate solution to carry out a catalytic reaction for 1 hour to complete the degradation of norfloxacin in the water.

[0089] Control group 1: The acidified halloysite material (HNT) was used to replace the iron-based halloysite material (Fr-HNT) with the functional unit structure, and other conditions were the same.

[0090] Control group 2: The supported iron-based catalyst (Fe2O3-HNT) was used to replace the functional unit structured iron-based halloysite material (Fr-HNT), and other conditions were the same.

[0091] During the catalytic reaction, the residual concentration of norfloxacin in the solution was measured by sampling, and the removal rate of norfloxacin under different systems was calculated, as shown in Table 1 and Figure 6 shown.

[0092] Table 1 Removal rate of norfloxacin under different systems

[0093] Example 4 Control group 1 Control group 2 Removal rate of norfloxacin 98.7% 2.3% 40%

[0094] As can be seen from Table 1, the functional element-structured iron-based halloysite material prepared by the present invention has a removal rate of norfloxacin in water of more than 98% within a reaction time of 1 hour, which is far superior to the ability of the acid-activated halloysite material (HNT) to activate persulfate, and is also far higher than the supported iron-based catalyst prepared in Comparative Example 1. This shows that the functional element-structured iron-based halloysite material prepared by the present invention has the advantages of large specific surface area, a large number of active sites, excellent catalytic performance, good structural stability, etc. It is a low-cost material that can effectively remove emerging pollutants in water, and can be widely used to activate persulfate and effectively remove emerging pollutants in water.

[0095] Figure 6 This is a comparison chart of the removal of norfloxacin by the iron-based halloysite material (Fr-HNT) with functional element sequence in Example 4 of the present invention, the acidified halloysite material (HNT), and the supported iron-based catalyst (Fe2O3-HNT). Figure 6 It can be seen that the treatment efficiency of Fr-HNT for NOR is higher than that of Fe2O3-HNT and HNT, which indicates that the Fr-HNT of the present invention has better ability to activate persulfate to degrade pollutants than the halloysite material prepared from ordinary inorganic iron source and the original halloysite material.

[0096] Example 5

[0097] The invention discloses an application of an iron-based nanoclay material with a functional element sequence structure as a catalyst for persulfate in the degradation of emerging pollutants, specifically using the iron-based nanoclay material with a functional element sequence structure as a catalyst for persulfate to activate peroxydisulfate to degrade norfloxacin (NOR) in water, comprising the following steps:

[0098] Take 5 portions of the functional element sequenced iron-based halloysite material (Fr-HNT) prepared in Example 1, 10 mg each, and add them to norfloxacin (NOR) solutions with pH values ​​equal to 3, 5, 7, 9, and 11 respectively (the volume of these solutions is 100 mL, and the concentration is 5 mg / L), and then add 1 mL of 0.2 mol / L peroxydisulfate solution to carry out catalytic reaction for 1 hour to complete the degradation of norfloxacin in the water.

[0099] During the catalytic reaction, samples were taken to determine the residual concentration of norfloxacin in the solution, and the removal rate of norfloxacin under different pH conditions was calculated, such as Figure 7 shown.

[0100] Figure 7 This is a diagram showing the removal effect of norfloxacin on the iron-based halloysite material (Fr-HNT) with functional element sequence in Example 5 of the present invention under different pH conditions. Figure 7It can be seen that under different pH conditions, the iron-based halloysite material with functional element structure prepared by the present invention has good activation ability for peroxydisulfate, and achieves efficient removal of norfloxacin. It can be seen that the norfloxacin material prepared by the present invention can stably produce catalytic effect in a wide range of pH values, and has great potential in the application of actual water bodies.

[0101] Example 6

[0102] The invention discloses an application of an iron-based nanoclay material with a functional element sequence structure as a catalyst for persulfate in the degradation of emerging pollutants, specifically using the iron-based nanoclay material with a functional element sequence structure as a catalyst for persulfate to activate peroxydisulfate to degrade norfloxacin (NOR) in water, comprising the following steps:

[0103] Take 5 portions of the functional element sequenced iron-based halloysite material (Fr-HNT) prepared in Example 1, 10 mg each, and add them into norfloxacin (NOR) solutions with concentrations of 1 mg / L, 5 mg / L, 10 mg / L, 20 mg / L, and 50 mg / L, respectively (the volume of these solutions is 100 mL, and the pH is 6.5), and then add 1 mL of 0.2 mol / L peroxydisulfate solution to carry out catalytic reaction for 1 hour to complete the degradation of norfloxacin in the water.

[0104] During the catalytic reaction, the residual concentration of norfloxacin in the solution was measured by sampling, and the removal rate of norfloxacin of different concentrations by the functional element sequenced iron-based halloysite material (Fr-HNT) was calculated, such as Figure 8 shown.

[0105] Figure 8 This is a diagram showing the removal effect of different concentrations of norfloxacin by the iron-based halloysite material (Fr-HNT) with functional element sequence in Example 6 of the present invention. Figure 8 It can be seen that the iron-based halloysite material with functional element structure prepared by the present invention can have a very obvious treatment effect on norfloxacin within 10 mg / L under the preferred preparation conditions, using only a small amount of material and oxidant. Although the removal effect on 20 and 50 mg / L of norfloxacin is not good, the concentration of norfloxacin in actual wastewater is difficult to reach this concentration level. If there is high-concentration norfloxacin wastewater, the amount of material and oxidant used in the present invention can be appropriately increased. In summary, the iron-based halloysite material with functional element structure prepared by the present invention has a very large application potential in dealing with actual water bodies of norfloxacin.

[0106] It can be seen from the above results that, compared with conventional supported iron-based catalysts, in the present invention, by acidifying nanoclay and using ferrocene as a doped iron source, an iron-based nanoclay material with a functional element structure having a large specific surface area, a large number of active sites, excellent catalytic performance, and good structural stability can be prepared by pyrolysis. When used as a catalyst for persulfate to degrade emerging pollutants, it can achieve effective degradation of emerging pollutants. In particular, the iron-based nanoclay material with a functional element structure used is less affected by pH, can exert catalytic efficiency under a very wide range of pH conditions, and can show very high treatment efficiency and very good removal effect. It has the advantages of simple process, convenient operation, low cost, high treatment efficiency, good degradation effect, etc., and is of great significance for effectively removing emerging pollutants in the environment.

[0107] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing an iron-based nanoclay material with a functional element sequence, characterized in that: The following steps are involved: S1. Acidifying the nanoclay; S2, mixing the acidified nanoclay, ferrocene and organic solvent in step S1, stirring and drying to obtain a precursor; S3. Pyrolyzing the precursor obtained in step S2 to obtain an iron-based nanoclay material with a functional element sequence.

2. The preparation method according to claim 1, characterized in that: In step S1, the nanoclay is acidified with an acidic solution; the acidic solution is at least one of an acetic acid solution, a sulfuric acid solution, and a nitric acid solution; and the volume ratio of the acid to water in the acidic solution is 1:2-5.

3. The preparation method according to claim 2, characterized in that: In step S1, the nanoclay is at least one of halloysite, sepiolite and montmorillonite.

4. The preparation method according to claim 2, characterized in that: In step S1, the acidification time is 12h to 24h.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step S2, the mass ratio of the acidified nanoclay to the ferrocene is 1 to 5:1; the organic solvent is at least one of ethanol, methanol and acetone; and the stirring time is 4 to 24 hours; In step S3, the pyrolysis is carried out in a protective atmosphere; the gas in the protective atmosphere is any one of nitrogen, helium, neon and argon; the heating rate during the pyrolysis process is 5°C / min to 15°C / min; the pyrolysis temperature is 400°C to 600°C; and the pyrolysis time is 2h to 4h.

6. An iron-based nanoclay material with a functional element sequence, characterized in that: The functional element sequenced iron-based nanoclay material is prepared by the preparation method described in any one of claims 1 to 5.

7. The iron-based nanoclay material with functional element sequence structure according to claim 6, characterized in that: The iron-based nano-clay material with the functional element sequence structure comprises a nano-clay material doped with iron atoms; the nano-clay material is in a nano-tube structure.

8. Use of the iron-based nanoclay material with a functional element structure as claimed in claim 6 or 7 as a catalyst for persulfate in the degradation of emerging pollutants.

9. The use according to claim 8, characterized in that: The method uses an iron-based nanoclay material with a functional element structure as a catalyst for persulfate to degrade emerging pollutants in water, comprising the following steps: mixing the iron-based nanoclay material with a functional element structure, water containing emerging pollutants, and persulfate for catalytic reaction to complete the degradation of emerging pollutants in the water; the amount of the iron-based nanoclay material with the functional element structure added is 0.1g to 0.2g per liter of the water containing emerging pollutants; and the initial concentration of persulfate in the catalytic reaction system is controlled to be 2mM.

10. The use according to claim 9, characterized in that: The initial concentration of emerging pollutants in the water body containing emerging pollutants is ≤10 mg / L; the emerging pollutants in the water body containing emerging pollutants are at least one of perfluorinated compounds, antibiotics, microplastics, and endocrine disruptors; the antibiotic is norfloxacin; the persulfate is peroxymonosulfate and / or peroxydisulfate; the time of the catalytic reaction is ≥2 min.

Citation Information

Patent Citations

  • Anionic type photocatalyst and preparation method thereof

    CN107754865A

  • Carbon encapsulation defect iron nano-catalyst, preparation method thereof and application of carbon encapsulation defect iron nano-catalyst in catalyzing peroxymonosulfate to degrade emerging pollutants

    CN110947385A

  • Cobalt ferrite / montmorillonite / C catalyst capable of efficiently activating persulfate as well as preparation method and application of cobalt ferrite / montmorillonite / C catalyst

    CN112473670A

  • Preparation method of clay-modified biomass-based high-loading-capacity monatomic catalyst

    CN118698543A

  • Preparation method and application of zero-valent aluminum / iron-bearing clay composite for catalyzing persulfate to oxidize organics

    US11534738B1